2014
DOI: 10.1088/0004-637x/787/1/22
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-Instrument Analysis of Sunspot Umbrae

Abstract: The recent solar minimum and rise phase of solar cycle 24 have been unlike any period since the early 1900s. This article examines some of the properties of sunspot umbrae over the last 17 years with three different instruments on the ground and in space: MDI, HMI and BABO. The distribution of magnetic fields and their evolution over time is shown and reveals that the field distribution in cycle 24 is fundamentally different from that in cycle 23. The annual average umbral magnetic field is then examined for t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 24 publications
0
16
1
Order By: Relevance
“…Watson et al (2011) studied cycle 23 using SOHO MDI data and reported a long-term trend in the umbral field strength of about −24 G yr −1 . Watson et al (2014) used data of MDI, HMI, and Kitt Peak and found a rate of about −22 G yr −1 between 1996 and 2013, about twice higher than the rate we find.…”
Section: Long-term Variation Of the Umbral Field Strength And Intensitycontrasting
confidence: 70%
See 3 more Smart Citations
“…Watson et al (2011) studied cycle 23 using SOHO MDI data and reported a long-term trend in the umbral field strength of about −24 G yr −1 . Watson et al (2014) used data of MDI, HMI, and Kitt Peak and found a rate of about −22 G yr −1 between 1996 and 2013, about twice higher than the rate we find.…”
Section: Long-term Variation Of the Umbral Field Strength And Intensitycontrasting
confidence: 70%
“…Since the mainly vertical field lines in umbra partially quench the convection, several authors searched for a relation between umbral intensity and umbral field strength. Kopp & Rabin (1992), Penn et al (2002), Schad & Penn (2010), and Rezaei et al (2012) presented this relation for different samples of sunspots in the near-infrared wavelength range, while among others, Norton & Gilman (2004), Leonard & Choudhary (2008), Pevtsov et al (2011), Watson et al (2014), Kiess et al (2014), and Schad (2014) made similar analyses in the visible wavelength range.…”
Section: Introductionmentioning
confidence: 59%
See 2 more Smart Citations
“…also, , Watson et al (2009Watson et al ( , 2014, Livingston and Watson (2015), Rezaie et al (2015), there was initial evidence that the average maximum umbral magnetic field strength decreased steadily from 1999-2005. This decrease is now understood to have been biased by a then observational interest in large spots.…”
Section: Umbral Magnetic Fieldsmentioning
confidence: 90%